Hepatoblastoma With Rubinstein-Taybi Syndrome: A Rare Association. (28th October 2020) - Arshi, J; Allison, D; Rao, D
Abstract: Introduction/Objective: Hepatoblastoma is a malignant neoplasm of liver, exclusively seen in pediatric population. It has been known to occur with various syndromes like Li-fraumeni, Beckwith-Wiedemann, and Simpson-Golabi- Behmel among others. Small undifferentiated cells and macro-trabecular pattern with increased mitotic activity and AFP>100 are associated with unfavorable prognosis. Rubinstein-Taybi syndrome is a rare genetic disease. Even though there has been intensive research on the genetic and epigenetic function of the CREBBP and EP300 genes in animal models, the etiology of this rare and devastating syndrome is largely unknown. Hepatoblastoma with Rubinstein-Taybi syndrome is an extremely rare occurrence. Methods: Here we present an incidental case of Hepatoblastoma with Rubinstein-Taybi syndrome Results: A 17-month-old Caucasian female with Rubinstein-Taybi syndrome, was found to have an incidental 1.1 cm nodule in the right lobe of liver. Her AFP was elevated (244.9ng/ml). Hepatic resection revealed a well-circumscribed tan white mass, measuring 3.5 cm in the greatest dimension. On microscopy, uniform round to cuboidal cells resembling fetal hepatocytes, with finely granular cytoplasm, small round nuclei, and indistinct nucleoli were seen. The cells were arranged in solid sheets and scant trabecular arrangement separated by narrow sinusoids. The tumor displayed predominantly fetal histology, with rare embryonal and small undifferentiated cell nests. The diagnosis of Hepatoblastoma was made. The patient underwent chemotherapy and was doing well at 5-years follow-up. Conclusion: Extensive screening of patients in recent times has revealed mutations in CREBBP and EP300 in only around 50% of cases. The genetic and epigenetic associations of the syndrome in the remaining half of cases remains to be identified. Hepatoblastoma with Rubinstein-Taybi Syndrome is an extremely rare occurrence and might shed some light on other genes that could be involved in this syndrome. Further studies to review the mutation spectrum to understand the causative molecular mechanisms are deemed essential.